2015
DOI: 10.4314/njt.v35i1.23
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Transient Stability of Nigerian 330kv Transmission Network Using Static Var Compensation Part I: The Base Study

Abstract: In this paper, the base study for improving the transient In this paper, the base study for improving the transient In this paper, the base study for improving the transient In this paper, the base study for improving the transient stability of Nigerian 330kV transmission network using stability of Nigerian 330kV transmission network using stability of Nigerian 330kV transmission network using stability of Nigerian 330kV transmission network using Static Var Compensation (SVC) is conducted with the focus of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…respectively. The voltage profile for the unfortified system of Figure 3 and as depicted in Table 3 shows that the following buses have voltage magnitudes below the acceptable ±5% of the normal 330 kV voltage magnitude profile (1.0 p.u) [19]: 3(Kaduna), 4(Kano), 6(Makurdi), 9(Jos), 28(Ayede) and 31(Sakete). The result of the power flow also showed that the total real power generation in p.u.…”
Section: Simulation Results Of Nigerian 48-bus Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…respectively. The voltage profile for the unfortified system of Figure 3 and as depicted in Table 3 shows that the following buses have voltage magnitudes below the acceptable ±5% of the normal 330 kV voltage magnitude profile (1.0 p.u) [19]: 3(Kaduna), 4(Kano), 6(Makurdi), 9(Jos), 28(Ayede) and 31(Sakete). The result of the power flow also showed that the total real power generation in p.u.…”
Section: Simulation Results Of Nigerian 48-bus Systemmentioning
confidence: 99%
“…where is the reference reactance, Xc is the function of state variables Vi, Vj and Vse. The objective function can be written as ∆ ( ) = ( ) − = 0 (19) where = [ , , , , , ]…”
Section: Reactance Controlmentioning
confidence: 99%
“…Tests carried on 6-bus, IEEE 14-bus, IEEE 30-bus, and IEEE 57-bus test systems were successful but the work is more of theoretical assumptions. In the study [15], a static var compensation (SVC) was conducted on the Nigerian 330kV transmission network with the focus of developing indices for improving the transient stability using an appropriate size to locate SVC within the network. The result showed an improved voltage profile and stability of network but the authors did only consider the optimal size of the DG.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the power system interconnected network has become more complex and difficult to manage due to increase in load demand which has forced electric utilities to either operate the system beyond or close to their thermal stability limit [1]. This development of operating the system close to its limit will definitely have a negative effect on the system security [2]. Security of power system refers to its ability to withstand disturbances without losing synchronism.…”
Section: Introductionmentioning
confidence: 99%